Reaction & affirmation: the albanian national awakening in Balkan Peninsula (1878-1913) - Melo, Tiago Valêncio de (Revista de Ciências do Estado, 2019)
In 1878, with the victory of the Russian Empire in the Russo-Turkish War, a new scenario was drawn in the geopolitics of the Balkan Peninsula. After four long centuries of Ottoman judgment, the peoples of the peninsula envisioned the possibility of a new political arrangement. However, although theoretically liberated from the dominion of Istanbul, the peoples of the peninsula still could not be considered as responsible for tracing the lines of their own destiny. The strategic location of the peninsula - located in the transition between West and East - made the region a stage of dispute of the great powers. After 400 years of control by an outside force, the fate of the peoples of the region was again in the hands of exogenous forces. In this sense, the present work aims to analyze the development of Albanian nationalism within the troubled and volatile scenario of the Balkan Peninsula during the final stage of the nineteenth and early twentieth centuries. The hypothesis presented for the research is that the emergence of Albanian nationalism consists of a movement of a reactive character, facing a scenario of rupture of the status quo in the region.